Smart Greenhouse: Solusi Alternatif Pertanian di Nagari Parambahan, Bukit Sundi, Kabupaten Solok - Wellyalina; Rahmi Awalina; Meisilya Erona; Joardan Lasop; Faldiyo Alghifary; Arif Rizkika Putra; Satria Pratama Eka Putra; Ikhsan Ismail (Warta Pengabdian Andalas, 2024)
Nagari Parambahan is a village in the Bukit Sundi subdistrict, Solok Regency, West Sumatra Province, where most of the population works in agriculture. A greenhouse is a building with a transparent structure that serves as a facility for plant cultivation. Innovations have been made to enhance efficiency and production results while maintaining environmental sustainability by implementing an innovative greenhouse system to optimize the greenhouse. The community service in Nagari Parambahan aims to socialize the concept of smart greenhouses to optimize agricultural efficiency and results while ensuring environmental sustainability in Nagari Parambahan. The series of community service activities consists of four parts: opening, smart greenhouse socialization, handover of smart greenhouse equipment/design, and a visit to the smart greenhouse location. The event went smoothly, with participation from the people of Nagari Parambahan, and it was attended by local government officials, lecturers and students.